Practice of common ethical standards in the field of counseling and psychotherapy in mainland China. Issue 3 (3rd April 2023) - An, Qin; Lin, Xiubin; Sang, Zhiqin; Qian, Mingyi
ABSTRACT: This paper will first introduce the development of professional ethics of counseling and psychotherapy in mainland China. Ethical awareness is often limited due to variations in training experiences. Aligning with ethics codes can also bring challenges due to nuances within Chinese culture. Furthermore, the authors discuss the ethical challenges regarding the principles of multiple relationships, informed consent, and confidentiality in the context of Chinese culture. These ethical issues are often discussed within an individualistic cultural frame and presentation from a collectivist culture offers a unique perspective in the ethics literature.